From text to screenplay (gendering the nation in Mariam Naoum's literary adaptations) - Serhan, May (AUC Knowledge Fountain, 2018)
Mariam Naoum's literary adaptations to television in the aftermath of the 2011 Egyptian uprising have carried wide cultural, political and literary implications, especially where the "woman question" is concerned. With Islamism and militarism both threatening to exclude a wide sector of women from the historical narrative of the uprising and the subsequent nation-building process, and with a male-dominated literary establishment that systematically relegates women to secondary roles, Naoum's writing re-affirmed gendered agency both on the level of social engagement and authorship. Chapter one of the thesis provides the theoretical framework and historical backdrop necessary for understanding how female writing can contest various male-sanctioned boundaries so as to define gender, cultural and national identities on its own terms. Chapters two, three and four examine the various applications of these ideas. Chapter two focuses on how the female writer turns the stagnant political moment of Osama Anwar Okasha's novel, Munkhafad al-Hind al-Mawsimyy into a hopeful narrative empowered by women that are responsible for bringing about change to the nation. Chapter three looks at how a completely disenfranchised female protagonist in Sonallah Ibrahim's Dhat is freed in the adaptation to represent a nation that is in full possession of itself and its future. Finally, chapter four is a critical reading of how Naoum reinterprets gendered agency in Fathiyya al- Assal's Sign al-Nisa' through a process of meaning construction, which breaks down many of the static and disabling labels attached to gender. By capitalizing on the power of adaptation, of television drama, and of Ramadan's high access to audiences of all stripes, Mariam Naoum writes gendered agency into the nation at a critical time in groundbreaking ways.